The Effects of Inflation Surprises and Uncertainty on Real Wages - Ratti, Ronald A. (The Review of Economics and Statistics, 1985)
This paper presents a partial equilibrium model of the labor market that allows the real wage, the expected real wage, and the level of employment to be expressed as functions of unexpected inflation, inflation uncertainty, and supply shocks. Regression equation estimation using U.S. data from 1948 to 1980 suggests that inflationary surprises and uncertainty cause countercycical movement in real wages. Various supply shock variables are introduced. The findings suggest the importance of oil shocks as compared with measures based on food or imports, but only after 1973.